Pemasangan Lampu Sorot dan Led Strip Dengan Pengoperasian Otomatis di Gapura Klaster SPI Sukun Kota Malang - Imron Ridzki; Muhammad Fahmi Hakim; Sukamdi; Mudjiono; Bakti Indra Kurniawan (Elposys: Jurnal Sistem Kelistrikan, 2021)
Installation of spotlights and LED strips with automatic operation at the entrance gate of the SPI Cluster RT.10 RW.04 Bandungrejosari Village, Sukun District Malang City is based on the absence of lighting contained in the writing of the Sukun Pondok Indah Cluster (SPI) so that many guests or couriers who are not aware of the housing. With the installation of spotlights and LED strips, it is hoped that the writing on the gate of the Sukun Pondok Indah cluster will be bright and visible so that guests or couriers can immediately know about the housing. Then people can see when installing spotlights and LED strips with automatic operation, they hope that people can install lighting installations automatically in their respective homes correctly and according to standards. Then people do not need to operate the ON / OFF spotlights and LED strip every day. That way, the benefits of installing spotlights and LED strips with automatic operation, people don't need to ON / OFF the lighting every time.